Induction of Stearoyl-CoA 9-Desaturase 1 Protects Human Mesenchymal Stromal Cells Against Palmitic Acid-Induced Lipotoxicity and Inflammation - Dalla Valle, Antoine; Vertongen, Pascale; Spruyt, Delphine; Lechanteur, Jessica; Suain, Valérie; Gaspard, Nathalie; Brion, Jean-Pierre; Gangji, Valérie; Rasschaert, Joanne (Frontiers in Endocrinology, 2019)
In bone diseases such as osteonecrosis and osteoporosis, a shift toward a preferential differentiation of mesenchymal stromal cells (MSC) into adipocytes at the expense of the osteoblastic lineage is described, leading to excessive accumulation of adipocytes in the bone marrow of the patients. The influence of cytokines and adipokines secreted by adipocytes on skeletal health is already well-documented but the impact of free fatty acids release on bone cell biology and viability is an emerging concept. We have previously demonstrated that the saturated fatty acid (SFA) palmitate (Palm) is cytotoxic for human MSC (hMSC) and osteoblasts whereas oleate (Ole), a monounsaturated fatty acid (MUFA), has no toxic effect. Moreover, Ole protects cells against lipotoxicity. Our observations led us to propose that the toxicity of the SFA is not correlated to its intracellular accumulation but could rather be related to the intracellular SFA/MUFA ratio, which finally determines the toxic effect of SFA. Therefore, in the present study, we have investigated the potential protective role of the enzyme stearoyl-CoA 9-desaturase 1 (SCD1) against the deleterious effects of Palm. SCD1 is an enzyme responsible for desaturation of SFA to MUFA; its activation could therefore lead to modifications of the intracellular SFA/MUFA ratio. In the present study, we showed that hMSC express SCD1 and liver X receptors (LXRs), transcription factors regulating SCD1 expression. Human MSC treatment with a LXRs agonist triggered SCD1 expression and drastically reduced Palm-induced cell mortality, caspases 3/7 activation, endoplasmic reticulum stress and inflammation. We also observed that, in the presence of Palm, the LXRs agonist provoked lipid droplets formation, augmented the total cellular neutral lipid content but decreased the SFA/MUFA ratio when compared to Palm treatment alone. Addition of an inhibitor of SCD1 activity abrogated the positive effects of the LXRs agonist, suggesting that SCD1 could play a key role in protecting hMSC against lipotoxicity.